Biodiesel in India: value chain organisation and policy options for rural development - Tilman Altenburg; Hildegard Dietz; Matthias Hahl; Nikos Nikolidakis; Christina Rosendahl; Kathrin Seelige (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
India promotes the production of biodiesel from tree-borne oilseeds. This is seen as an option for substituting fossil fuels, reducing CO2 emissions, afforesting wastelands, and generating rural employment. Critics, however, claim that it may lead to food scarcity and seizure of common lands by corporate investors. This report shows that biodiesel production in India has mainly positive effects. As it is promoted on the basis of non-edible oil seeds on marginal lands, the risks of driving up prices for edible oil or crowding out food production are relatively low. However, the actual development effects may vary greatly, depending on how value chains are organized. This study identifies 13 different ways of organizing biodiesel value chains, ranging from cultivation on large plantations to contract farming, smallholder production for rural electrification, and social forestry projects – each of them having different effects on income generation, participation and empowerment, food security, natural resources management, and climate change. To date, biodiesel production is not a lucrative business, except for some niche markets. This may change in the future, depending on fossil fuel prices, government pricing policies, and agricultural yields. The study describes and assesses a range of federal and state policies aimed at enhancing the economic viability of biodiesel production and ensuring positive development effects.
Keywords: 330